Multiple oligodendroglioma with pseudoprogression - Matsuyama, Junko (Medknow Publications & Media Pvt Ltd, 2012)
A 72 year-old male hospitalized with aphasia, abnormal behavior, and rapidlyprogressive dementia.Magnetic resonance imaging (MRI) enhanced by contrast media demonstrated multiplebrain tumors in left parietal lobe and left paraventricular region. Biopsy was performed,andhistopathological examination and genetical evaluation revealed anaplasticoligodendroglioma. Local radiation 50Gy was given, and Temozolomide via orallyadministered for 42 days. After the chemoradiotherapy, even though the parietal tumorshowed lessening of the size, enlargement of the tumor in the left paraventricularregion was observed, and we considered that phenomenon was pseudoprogression. 5courses of Temozolomide therapy was added, but cerebellar tumor appeared andenlarged with hydrocephalus, and died 1 year and 3 months after the firsthospitalization.